Validated Guidelines for Stakeholder Engagement with the Agriculture Sector in Select Countries of the Caribbean - St. Ville, Lyndell (Inter-American Institute for Cooperation on Agriculture (IICA), 2023)
This document provides an overview of the Guidelines for Stakeholder Engagement in the Agriculture Sector in select Caribbean countries, developed as part of the IICA Green Climate Fund Readiness Support Project. The guidelines were developed through a three-phased process, including a desk review, assessment of stakeholder engagement, and participatory consultative process with national stakeholders. The study found that most stakeholders in the agriculture sector had been involved in broader climate change processes rather than GCF-financed processes, and only a small percentage reported involvement in GCF-financed processes. NDAs and AEs appeared to have fostered interest in GCF climate financing and generated goodwill in the agriculture sector about participating in stakeholder engagement activities.